Human Rights and Athlete Advocacy: The Role of Sports Organizations in Protecting Athletes in Indonesia (Indonesian Sports Justice Review, 2024)
As the sports industry in Indonesia continues to grow, so too does the need for effective mechanisms to protect athletes’ rights. This paper explores the role of sports organizations in advocating for athlete welfare and protecting their human rights, particularly in a country where issues such as exploitation, inadequate health services, and unethical management practices are prevalent. By examining case studies of high-profile Indonesian athletes and investigating the policies of key sports organizations, the study highlights the challenges athletes face in terms of labor rights, personal safety, and representation. The paper also considers the role of sports unions and advocacy groups in championing athlete rights and discusses the legal frameworks that support or hinder these efforts. The study concludes with recommendations for enhancing athlete protection, including stronger regulations, independent oversight bodies, and comprehensive athlete support programs.